CRITERIA FOR TEACHING NORMAL ENGLISH PRONUNCIATION STANDARDS: 1-SON 3-TO’PLAM IYUL 2023 yil - TSUULL, senior student, Translation theory and practice faculty, Gulimboyeva Nozima Azimboy qizi (Ta'lim innovatsiyasi va integratsiyasi, 2023)
The processes of globalization and integration taking place all over the world today increase the need to learn foreign languages among the peoples of the world. The internationalization of the English language, especially in developing and other countries, will greatly help the development of internal and external relations, the dissemination of scientific and technical achievements. This article compares British and American accent variants of words, one of the main problems in teaching